PROTEIN QUALITY OF FOODS. II. Application of Acceptable Parameters to Assess and Improve Diets - Gloria, Lydia A. (Annals of Tropical Research, 1981)
Poor quality of protein in copra meal diet was attributed more to poor digestibility than to poor nitrogen retention; in mungbean diet, it was due more to poor nitrogen retention than to poor digestibility. Nitrogen utilization of both diets decreased when protein levels were increased. The copra meal-fish meal mixture greatly increased its nitrogen utilization when diluted with protein, but further improvement was observed when 0.07% methionine was added to the mixture. In mungbean diet, supplementation with methionine greatly improved its nitrogen retention. The deleterious effect caused by feeding high level of copra meal may be attributed to high excretion of urea.